Ginger extract as an alternative to thrips (Thrips tabaci) control in hydroponic lettuce - Silva, Synara; Gouvêia, Marcelo Antônio de Sousa; Silva, Sylmara; Gonçalves, Luciano Donizete; Pereira, Rafael (Revista Agrogeoambiental, 2021)
Ginger has a large number of essential oils, zingiberene is the major substance found in it, which may be linked to the insecticidal activity of the plant. Therefore, it can be a viable alternative to replace the use of pesticides for pest control. The objective of this work was to evaluate the use of this ginger-based extract in hydroponic lettuce as an alternative to thrips control. The experiment was carried out in a randomized block design, with five treatments and four replications. The treatments used were the concentrations of 0 %, 20 %, 40 %, 60 %, and 80 % weight/volume of aqueous extract. After 45 days of sowing, the ginger plant extract was applied to the lettuce plants every seven days. A population of thrips was monitored using adhesive traps attached above each experimental plot once a week until harvest. In addition, fresh mass weight, shoot height, and incidence of direct damage to the crop were evaluated. Regarding thrips monitoring, no differences were observed indicating the uniformity of the population level among the lettuce parcels. For the evaluation of weight and fresh mass, no differences were observed regarding the treatments. However, from the concentration of 60 %, it was observed the lowest averages of plants with direct damage, showing that the higher the concentration of the solution the lesser insect feeding. Accordingly, the use of ginger plant extract in hydroponic lettuce becomes a promising alternative for reducing thrips feeding on lettuce.